Ekonomiczne aspekty funkcjonowania małych elektrowni wodnych - Bukowski, Marcin (Economic Aspects of Functioning of Small Hydroelectric Power Stations, 2009)
Poland's accession to the EU has caused a necessity of harmonising Polish law with the European law also in the field of energy law. It also enforces the achievement of 7.5% share of energy from alternative sources in the total energy consumption in 2010. This article presents an analysis of energy production on a sample of 17 small hydroelectric power stations, located in the lowland but hilly northern-central part of Poland. The analysis covers a period from 2003 to 2006. The research was based on the information about economic and technical parameters of the analysed objects. The influence of installed power on the revenue from energy sale is analyzed. The reduction of pollution resulting from the replacement of a conventional power station with a hydropower station is estimated in order to calculate its replacements social benefits.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 83, s. 134-144